On Chekhov’s Theatre in Catalunya - AMIRAGHYAN, HASMIK (Bulletin of Yerevan University H: Russian Philology, 2021)
The article resumes the history of translations from Russian literature in Catalunya, focusing on the assimilation of A. Chekhov’s theatre on the Catalan stage. Based on studies referring to Catalan translations of Russian works of literature and, in particular, plays by Chekhov, as well as on theatre reviews published in different periodicals, the article presents the evolution of the reception of Chekhov’s works in Catalunya through the years.
Keywords: Russian literature, Catalan translations, reception of Chekhov’s theatre in Catalunya, horizon of expectations, assimilation